Clinical Findings of Specular Microscopy Images in Cytomegalovirus Corneal Endotheliitis. Issue 3 (May 2022) - Kobayashi, Reiko; Hashida, Noriyasu; Maruyama, Kazuichi; Nishida, Kohji
Abstract : Purpose: The aim of this study is to evaluate the usefulness of specular microscopy as an alternative diagnostic tool for cytomegalovirus (CMV) corneal endotheliitis. Design: A retrospective study. Methods: One hundred and four patients with clinical manifestations of infectious corneal endotheliitis, iridocyclitis, and retinitis were included in this study. The presence of CMV deoxyribonucleic acid (DNA) was confirmed by multiplex polymerase chain reaction (PCR). Viral load was measured using real-time PCR. Corneal endothelium was observed by specular microscopy. The medical records and clinical manifestations of the patients were retrospectively reviewed and linked with the PCR results. Results: Seventeen of 104 cases were CMV endotheliitis and/or iridocyclitis and had no history of intraocular surgery or corneal transplantation. There was a negative correlation between viral load and corneal endothelial cell counts. In 14 of 17 cases, owl's eye cells were observed by specular microscopy. The corneal endothelial cell counts were significantly reduced in the cases in which owl's eye cells were observed. Conclusions: In CMV endotheliitis, owl's eye cells were observed by specular microscopy with high probability (82%). Corneal endothelial cells significantly decreased when owl's eye cells were observed by specular microscopy. Specular microscopy represents a useful noninvasive auxiliary tool for diagnosing and monitoring CMV corneal endotheliitis.